Glycerol Trinitrate Acts Downstream of Calcitonin Gene-Related Peptide in Trigeminal Nociception—Evidence from Rodent Experiments with Anti-CGRP Antibody Fremanezumab - Benedicter, Nicola; Vogler, Birgit; Kuhn, Annette; Schramm, Jana; Mackenzie, Kimberly D.; Stratton, Jennifer; Dux, Mária; Meßlinger, Karl (Cells, 2024)
Calcitonin gene-related peptide (CGRP) and nitric oxide (NO) have been recognized as important mediators in migraine but their mechanisms of action and interaction have not been fully elucidated. Monoclonal anti-CGRP antibodies like fremanezumab are successful preventives of frequent migraine and can be used to study CGRP actions in preclinical experiments. Fremanezumab (30 mg/kg) or an isotype control monoclonal antibody was subcutaneously injected to Wistar rats of both sexes. One to several days later, glyceroltrinitrate (GTN, 5 mg/kg) mimicking nitric oxide (NO) was intraperitoneally injected, either once or for three consecutive days. The trigeminal ganglia were removed to determine the concentration of CGRP using an enzyme-linked immunosorbent assay (ELISA). In one series of experiments, the animals were trained to reach an attractive sugar solution, the access to which could be limited by mechanical or thermal barriers. Using a semi-automated registration system, the frequency of approaches to the source, the residence time at the source, and the consumed solution were registered. The results were compared with previous data of rats not treated with GTN. The CGRP concentration in the trigeminal ganglia was generally higher in male rats and tended to be increased in animals treated once with GTN, whereas the CGRP concentration decreased after repetitive GTN treatment. No significant difference in CGRP concentration was observed between animals having received fremanezumab or the control antibody. Animals treated with GTN generally spent less time at the source and consumed less sugar solution. Without barriers, there was no significant difference between animals having received fremanezumab or the control antibody. Under mechanical barrier conditions, all behavioral parameters tended to be reduced but animals that had received fremanezumab tended to be more active, partly compensating for the depressive effect of GTN. In conclusion, GTN treatment seems to increase the production of CGRP in the trigeminal ganglion independently of the antibodies applied, but repetitive GTN administration may deplete CGRP stores. GTN treatment generally tends to suppress the animals’ activity and increase facial sensitivity, which is partly compensated by fremanezumab through reduced CGRP signaling. If CGRP and NO signaling share the same pathway in sensitizing trigeminal afferents, GTN and NO may act downstream of CGRP to increase facial sensitivity.
CRIS-Team Scopus Importer:2024-04-26
Keywords: calcitonin gene-related peptide; CGRP concentration; CGRP release; fremanezumab; glycerol trinitrate; migraine pain; monoclonal antibody; rat

Semi-Automated Recording of Facial Sensitivity in Rat Demonstrates Antinociceptive Effects of the Anti-CGRP Antibody Fremanezumab - Benedicter, Nicola; Meßlinger, Karl; Vogler, Birgit; Mackenzie, Kimberly D.; Stratton, Jennifer; Friedrich, Nadine; Dux, Mária (Neurology International, 2023)
Migraine pain is frequently accompanied by cranial hyperalgesia and allodynia. Calcitonin gene-related peptide (CGRP) is implicated in migraine pathophysiology but its role in facial hypersensitivity is not entirely clear. In this study, we investigated if the anti-CGRP monoclonal antibody fremanezumab, which is therapeutically used in chronic and episodic migraines, can modify facial sensitivity recorded by a semi-automatic system. Rats of both sexes primed to drink from a sweet source had to pass a noxious mechanical or heat barrier to reach the source. Under these experimental conditions, animals of all groups tended to drink longer and more when they had received a subcutaneous injection of 30 mg/kg fremanezumab compared to control animals injected with an isotype control antibody 12–13 days prior to testing, but this was significant only for females. In conclusion, anti-CGRP antibody, fremanezumab, reduces facial sensitivity to noxious mechanical and thermal stimulation for more than one week, especially in female rats. Anti-CGRP antibodies may reduce not only headache but also cranial sensitivity in migraineurs.
CRIS-Team Scopus Importer:2023-07-28
Keywords: behavioral model; calcitonin gene-related peptide; fremanezumab; mechanical sensitivity; migraine symptoms; monoclonal antibody; thermal sensitivity